Auxin Response Factors Are Ubiquitous in Plant Growth and Development, and Involved in Crosstalk between Plant Hormones: A Review - Xiaohong Kou; Xiaoyang Zhao; Bingda Wu; Chao Wang; Caie Wu; Sen Yang; Jiaqian Zhou; Zhaohui Xue (Applied Sciences, 2022)
Auxin response factors (ARFs) are an important family of transcription factors involved in the exertion of auxin in plants and play a key role in regulating the growth and development of plant nutritional and reproductive organs such as roots, stems, leaves, flowers, fruits, and seeds. Foods of plant origin occupy an important place in the nutritional structure of the human diet, and the main edible parts of different plants vary. In this paper, we review recent research reports on ARFs and summarize its role in the regulation of leaf, flower, root, and fruit growth, as well as other important life activities. We also present the challenges and opportunities that ARFs will present in the future. It will be important to deepen our understanding of the mechanisms by which ARFs interact with other proteins or genes. In addition, it is worth considering that more technical tools should be put into the study of ARFs and that the research should be oriented towards solving practical problems. In the future, it is expected that the nutrition and function of plant-derived foods can be improved through gene editing and other means.